A Worldwide Perspective on Viticultural Zoning - Vaudour, E.; Shaw, A.B. (South African Journal of Enology and Viticulture, 2017)
This article reviews viticultural zoning concerns and issues, from a worldwide perspective. The needs of the everexpanding international wine market, and thus zoning objectives, have seen significant changes in recent years.  Consequently, more countries and individual wine-producing regions have been involved in zoning studies.  Although many of these studies were initiated in Europe, zoning needs reach far beyond the countries endowed with centuries-old viticultural history. The demarcation of registered designations of origin or protected geographical indications is one of the most obvious zoning aims. Viticultural zoning originated in the XIXth century in Europe, but is now widely applied in even the most recent emerging wine-growing countries of the New World. Other important zoning aims, not necessarily related to demarcating operations, often involve segmenting a vineyard territory into homogeneous units for pest management, land division, vineyard-restructuring operations, harvestquality management or site selection for new vineyards. The homogeneous units obtained through viticultural zoning are frequently referred to as ‘terroirs’. However, their spatial scale and the qualitative and quantitative methods of analysis may vary greatly, depending on the individual authors and the characteristics of the vinegrowing region, and consequently it is difficult to make international comparisons. Viticultural zoning studies can be divided broadly into two main approaches: the first approach is based largely on the geographic differentiation of wine, grape, or grapevine characteristics, while the second approach focuses on the geographical differentiation of land capability or vineyard suitability studies in which soil and climate are normally the key environmental variables used with varying degrees of importance. Although viticultural zoning is not always synonymous with mapping and spatial analysis, this practice is changing due to the enhanced use of geomatics. For example, digital mapping methods and remote sensing techniques have revolutionized viticultural zoning on all levels, ranging from the single plot to the regional level. On the field or local scale, the suitability approaches may include precision viticulture, which is mostly directed towards an understanding of grapevine ecophysiological functioning. On the regional or global scale, suitability approaches may be oriented towards the characterisation of broad geographical patterns of land use. The challenge with the different approaches is to compare the results derived at the regional level with those of the sample sites on the local scale. This paper provides some examples of the various approaches that are likely to enable zoning comparisons at the various spatial scales, including the international level.